Where's the high-tech? (Monthly Labor Review, 2003)
This article presents information on the concentration of high-tech workers across the U.S. as of September 2003. San Jose, California, had the highest concentration of high-tech workers in the U.S. in 2001 among metropolitan areas, with just over 10 percent of workers employed in high-tech occupations. Boulder-Longmont, Colorado, had the next highest share, at just below 10 percent, followed by Melbourne-Titusville-Palm Bay, Florida, which had a high-tech employment share of about 7 percent. Average annual wages in 2001 for high-tech occupations in the 10 metropolitan areas with the highest concentrations of high-tech workers ranged from $48,120 in Melbourne-Titusville-Palm Bay, Florida, to $79,800 in San Jose, California. In all of these areas, the high-tech occupations had wages at least 50 percent higher than the average for non-high-tech occupations. The term "High-tech workers," is defined for this analysis as workers in 36 occupations utilizing new technologies to the greatest extent.